Incretin Hormones, Thyroid Stimulating Hormone and Human Growth Hormone Responses During Ogtt in Newly Diagnosed T2DM Patients (Bangladesh Journal of Medical Biochemistry, 2019)
Several research groups have reported variable results about incretin effects of glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1(GLP-1), altered thyroid stimulating hormone (TSH) status, human growth hormone (hGH) deficiency and perturbed cytokines balances in type 2 diabetes mellitus (T2DM).The present case-control prospective interventional study was conducted investigating responses of incretin hormones (GIP, GLP-1), TSH and hGH to oral glucose tolerance test (OGTT) in newly diagnosed Bangladeshi T2DM patient. Blood samples were collected from 36 OGTT positive newly diagnosed T2DM patients as cases and 30 normal adults as controls at '0' minute (fasting) and at 2 hours after OGTT. Laboratory investigations were done and special parameters in serum, i.e. hGH, TSH, Insulin, GIP and GLP-1 were analyzed using enzyme immunoassay (EIA) kits. Statistical analyses were made by Student's 't' test using SPSS programm. T2DM patients (cases) had FBG and BG2Hr levels much higher than controls (p